The influence of fatigue on internal and external load using game-based drills in junior and adult male basketball players - Hulka, K.; Strnište, M.; Hrubý, M. (Acta Gymnica, 2022)
Background: Fatigue demonstrated by decreasing performance seems to occur towards the ends of periods of matches and can lead to a win or loss of the match.